2013
DOI: 10.1097/ss.0000000000000025
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Dynamics in the Conversion of a Secondary Forest Into a Rubber Tree Plantation in the Amazon Rainforest

Abstract: During the past several decades, extensive areas of the humid tropical Amazon have been cleared for the introduction of pasture or subsistence farming and later abandoned after a few years of use. An option for recovering these areas is the planting of rubber trees because it is a native tree that could restore conditions similar to those existing before the clearing. In addition, the high economic value of natural rubber is a source of income for small producers. In soil management under the Amazon conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
0
7
0
2
Order By: Relevance
“…In fact, many previous studies reported the depletion of soil organic matter and mineral nutrients by land use change from primary or secondary forests to rubber plantation (e.g., Li et al 2012, de Blécourt et al 2013, Kotowska et al 2015, Allen et al 2015, and the soil degradation in rubber gardens can also increase with an increase in the age of the rubber tree stand (e.g., Aweto 1987, 2001, Cheng et al 2007. In contrast, other reports delivered inconsistent results to those previously documented: the soil fertility under rubber farming was similar to that under primary and secondary forests (e.g., Tanaka et al 2009, Moreira et al 2013, and little loss or even enhanced content of organic matter and some nutrients in the soil were found during rubber cultivation (Guillaume et al 2016, N'Dri et al 2018, Peerawat et al 2018. These contradictory findings warrant further research on the changes in soil fertility caused by rubber plantation.…”
Section: Introductionmentioning
confidence: 94%
“…In fact, many previous studies reported the depletion of soil organic matter and mineral nutrients by land use change from primary or secondary forests to rubber plantation (e.g., Li et al 2012, de Blécourt et al 2013, Kotowska et al 2015, Allen et al 2015, and the soil degradation in rubber gardens can also increase with an increase in the age of the rubber tree stand (e.g., Aweto 1987, 2001, Cheng et al 2007. In contrast, other reports delivered inconsistent results to those previously documented: the soil fertility under rubber farming was similar to that under primary and secondary forests (e.g., Tanaka et al 2009, Moreira et al 2013, and little loss or even enhanced content of organic matter and some nutrients in the soil were found during rubber cultivation (Guillaume et al 2016, N'Dri et al 2018, Peerawat et al 2018. These contradictory findings warrant further research on the changes in soil fertility caused by rubber plantation.…”
Section: Introductionmentioning
confidence: 94%
“…This knowledge gap potentially undermines our attempts to manage P retention in wetland systems. Previous studies have shown that rhizodeposition can induce changes in the composition of soil microbial communities by altering the quality and distribution of available organic matter, which may affect P fractions over time (Marschner et al, 2001;Moreira et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…bras., Brasília, v.51, n.9, p.1061-1068, set. 2016 DOI: 10.1590/S0100-204X2016000900005 Durante muitas décadas, áreas extensivas da Amazônia têm sido desmatadas e, após poucos anos de uso, abandonadas (Cravo & Smyth, 1997;Moreira et al, 2013). Aumento populacional, exploração da madeira, conversão em pastagem, e em agricultura de subsistência são os principais vetores por esta transformação (Johnson et al, 2001).…”
Section: Introductionunclassified